The Political Economy of Industrial Policy in the Middle East and North Africa - Nabli, Mustapha K.; Keller, Jennifer; Nassif, Claudia; Silva-Jáuregui, Carlos (World Bank, Washington, DC, 2017)
In this paper, authors examine the political economy and consequences of industrial policy in the MENA region. How can the features of MENA’s industrial policy be explained? And what accounts for the fact that, against world trends, industrial policies in MENA countries didn’t followed the evolutionary path of industrial policies of other countries? Unlike in many other regions, industrial policy in MENA developed within the context of the region’s strong ‘social contract’ between the government and its people. Although industrial development was an objective, it at times took a backseat to the more important goals of social transformation and economic redistribution, which influenced not only the types and success of industrial policies adopted, but also critically influenced the balance of power among interest groups. Section two of the paper provides the theoretical framework for understanding the experience with industrial policy. Starting with a brief survey of the arguments used to justify industrial policy interventions, and drawing on various strands of the literature it provides a review of the various mechanisms and arguments which help understand the factors which determine the emergence and type of industrial policies observed and how they change. Using this framework section three reviews the experience of MENA countries during the 1950s to the 1970s and the emergence of state-dominated vertical industrial policy, where traditional/sector selective and sector specific policies have been used extensively. Section four attempts to explain the failure for industrial policy to change during the 1980s and 1990s. While the developing world has moved toward more market oriented policies and production systems that are dominated by the private sector and rely on market signals, MENA has maintained much of the old style industrial policies and high state intervention in the economy that characterized much of the developing world in the past. The final section five makes concluding remarks on the likely directions of industrial policy in the region. As internal and external forces shape the way industrial policies can be used in the globalized economy, the MENA region’s old style of industrial policy will need to adjust. The ultimate path of change will be determined greatly by each country’s initial conditions and individual political economy factors.